Land, Law, and Legitimacy: Unveiling the Evidentiary Power of Ownership Certificates in the Confluence of Islamic and Agrarian Legal Traditions - Emah Nikmah; Hamdan Azhar Siregar (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study examines the legal status of land ownership certificates from the perspectives of positive law and Islamic jurisprudence. It explores national procedures for land certification and Islamic concepts of ownership and evidence, such as ikrar (declaration), shahadah (witness testimony), and ihya al-mawat (revival of dead land). Using a qualitative, normative-juridical method, the research analyzes statutory land rules and Islamic legal principles. Findings show that land certificates have strong evidentiary value under national law. However, bureaucratic delays, high administrative costs, and maladministration hinder the process. In Islamic law, such certificates may be recognized as valid ownership proof if acquired lawfully and aligned with justice and public welfare (maslahah). Islamic jurisprudence also emphasizes clarity in property rights to prevent disputes and promote fairness. Ultimately, while the two legal systems operate on distinct foundations, they can be integrated to build a more just and legally certain framework for land ownership.